Vulnerabilidad entre derechos humanos y bioética. Relaciones tormentosas, conflictos insolutos - Kottow, Miguel (2012)
Vulnerability, human rights, and bioethics. Turbulentrelationships, unsolved conflicts.Vulnerability as potential harm has been confused with actual damage, leading to the improper conclusion that those already harmed, therefore wrongly called vulnerable, are considered unable to take care of their own interests. Fragile, but as yet unharmed, vulnerability is an anthropological trait that implies liberty and equality as proclaimed by human rights, as well as by the ethics fundamental to all human endeavors. The universality of human rights has been put to question, arguing that they can only be claimed by individuals who are recognized as citizens. Also, different cultures and specific social groups demand the recognition of rights that are respectful of their singularity, and therefore not universal.The fundamental rights to liberty need to be complemented by political and social rights that take care of actual needs, harms and disempowerment. This kind of language is proper to bioethics, a  discipline focused upon human interventions on vital processes, deliberating upon sensitive issues that require decisions as well as normative public policies of social practices that pertain to its realm of reflection.